The pattern of cycle of civilization: resemblance between Ibn Khaldun and Malik Bennabi’s views = Corak kitaran ketamadunan persamaan di antara pendapat Ibn Khaldun dan Malik Bennabi - Berghout, Abdul Aziz; Berghout, Zakia (IIUM Press, International Islamic University Malaysia, 2015)
There is very much resemblance between Ibn KhaldËn and Malik Bennabi’s views on the concept of the cycle of civilization. It is evident that the two thinkers main-tain that civilization in its rise and fall follows the cyclical pattern whereby a civiliza-tion commences its course in history, develops and reaches its peak and the then retro-gresses and declines leaving space for another civilization to commence its course. This is the pattern that governs civilization in history. The articles argues that it was Ibn KhaldËn, within the Islamic circles of thought, who first introduced the concept of the cycle of civilization and applied it to his own time revealing that “State”, as a unit of analysis, follows in its course a cycle that consists of several stages from its inception to decline and later to transition to other places. Later in the history of Islam, it was Malik Bennabi who took the intellectual burden of expanding Ibn KhaldËn’s model of the cy-cle. He further developed Ibn KhaldËn’s view and introduced his own approach to the study of the pattern of the cycle of civilization showing various phases of the develop-ment of civilization. This article focuses more on the view of Bennabi as he is a con-temporary thinker whose ideas are much more relevant to our present state of affairs.